A Facility-Based Study of the Impact of COVID-19 on Supply Chain Performance of HIV/AIDS Commodities in Anambra State, Nigeria - Johnson Okwudili Nweke; Chana Chapchet Robert; Sunday Odunke Nduka (International Journal of Supply Chain Management, 2023)
The COVID-19 pandemic and its induced lockdown resulted in huge disruptions that affected access to and availability of healthcare commodities at different levels of the supply chain system. An understanding of the pandemic impact in different areas will help in designing strategies to mitigate future disruptions. This study was designed to evaluate the supply chain performance of HIV/AIDS commodities through the review of key performance indicators in health facilities in Anambra State, Nigeria, during the COVID-19 pandemic lockdown. A facility-based cross- sectional study was conducted across 27 selected health facilities in the state. Facilities were selected using a stratified random sampling technique. Data was collected using a combination of a semi-structured questionnaire and observational checklists adapted from a previous study and the Logistics Indicators Assessment Tool (LIAT). Data obtained were analyzed using SPSS software (version 23). A total number of 44 focal personnel managing the HIV/AIDS supply chain in 17 secondary health centres (SHCs) and 10 primary health centres (PHCs) participated in the study. Tenofovir/Lamivudine/Dolutegravir (300/300/50mg) and Nevirapine 10mg/ml oral suspension were the two most available drugs at 85.19% and 78% respectively whereas Determine and Uni-Gold were the most available non- drug commodities at 92.59%, and 81.48% respectively during the lockdown period. The Stat-Pak test kit was stocked out in 30% of the facilities during the lockdown with emergency orders of at least one HIV commodity recorded in 37% of the facilities during this period. Expired products were recorded in 48% of the health facilities and this amounted to a loss of USD 4,027.25. The COVID-19 crisis exposed vulnerabilities in Anambra State's HIV/AIDS commodity supply chain. Instances of emergency orders, stock-outs, and wastage highlight the need for a more resilient system. Investing in an agile supply chain is crucial for ensuring uninterrupted access to essential healthcare commodities during disruptions.